Experimental investigation of anionic and cationic surfactants performance in clay-rich sandstones - Chongtian Wu; Zahraa Sabah Ghnim; M. Sudhakara Reddy; Girish Chandra Sharma; Haider Radhi Saud; Debasish Shit; Sachin Jaidka; Pushpa Negi Bhakuni; Ayat Hussein Adhab; Morug Salih Mahdi; Aseel Salah Mansoor; Usama Kadem Radi; et al. (Scientific Reports)
Abstract Enhancing oil recovery in clay-rich sandstone formations presents challenges such as low interfacial tension (IFT) and poor fine migration control, which severely impact permeability and recovery efficiency. This study introduces a novel sequential injection strategy using cationic (CTAB) and anionic (SDS) surfactants, leveraging their complementary mechanisms to address these limitations. The systematic investigation reveals how CTAB’s fine-stabilizing properties, followed by SDS’s superior IFT-reducing capabilities, optimize oil recovery in clay-rich sandstones. Zeta potential analysis revealed significant charge alterations (+ 12 mV for CTAB and − 43 mV for SDS), indicating stabilization of clay particles by CTAB and enhanced particle dispersion by SDS. IFT measurements demonstrated substantial reductions from 43 mN/m in brine to 1 mN/m and 1.2 mN/m for CTAB and SDS, respectively, while contact angle tests confirmed CTAB and SDS reduced the hydrophobicity of oil-aged sandstone surfaces, decreasing contact angles from 125° to 91° and 93°, respectively, after 28 days of exposure. In core flooding experiments, permeability improved significantly with CTAB (65 md), while sequential surfactant injection yielded a peak recovery factor (RF) of 81%, surpassing individual brine injections (53%). These findings represent a novel approach to enhancing oil recovery by systematically linking physicochemical properties to dynamic reservoir processes, offering critical insights into fines migration control, wettability alteration, and EOR optimization.